Penerapan Discovery Learning untuk Meningkatkan Historical Explanation dan Hasil Belajar Peserta Didik Kelas XII IPS di SMA K.H. Agus Salim Tahun Ajaran 2021/2022. - Ilfiana Firzaq Arifin (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2022)
History learning according to the 2013 curriculum has a goal, one of which is to develop historical skills (historical explanation) which is the basis for logical, creative, inspirational and innovative thinking skills. But the fact is that in schools there are still many historical subjects that are taught conventionally regardless of the learning objectives achieved, so the purpose of this research is the application of the Discovery learning model to improve historical explanation and student learning outcomes. The research location is at the KH. Agus Salim school in class XII IPS in the academic year 2021/2022. This research uses a CAR research design. The research was carried out for 2 cycles, namely cycle 1 and cycle 2. The data analysis used was quantitative and qualitative.